Procalcitonin‐guided antibiotic therapy: A systematic review and meta‐analysis. Issue 9 (17th August 2013) - Soni, Nilam J.; Samson, David J.; Galaydick, Jodi L.; Vats, Vikrant; Huang, Elbert S.; Aronson, Naomi; Pitrak, David L.
Abstract : BACKGROUND: The utility of procalcitonin to manage patients with infections is unclear. A systematic review of comparative studies using procalcitonin‐guided antibiotic therapy in patients with infections was performed. METHODS: Randomized, controlled trials comparing procalcitonin‐guided initiation, intensification, or discontinuation of antibiotic therapy to clinically guided therapy were included. Outcomes were antibiotic usage, morbidity, and mortality. MEDLINE, EMBASE, the Cochrane Database, National Institute for Clinical Excellence, the National Guideline Clearinghouse, and the Health Technology Assessment Programme were searched from January 1, 1990 to December 16, 2011. RESULTS: Eighteen randomized, controlled trials were included. Data were pooled into clinically similar patient populations. In adult intensive care unit (ICU) patients, procalcitonin‐guided discontinuation of antibiotics reduced antibiotic duration by 2.05 days (95% confidence interval [CI]: −2.59 to −1.52) without increasing morbidity or mortality. In contrast, procalcitonin‐guided intensification of antibiotics in adult ICU patients increased antibiotic usage and morbidity. In adult patients with respiratory tract infections, procalcitonin guidance significantly reduced antibiotic duration by 2.35 days (95% CI: −4.38 to −0.33), antibiotic prescription rate by 22% (95% CI: −41% to −4%), and total antibiotic exposure without affecting morbidity or mortality. A single, good quality study of neonates with suspected sepsis demonstrated reduced antibiotic duration by 22.4 hours ( P = 0.012) and reduced the proportion of neonates on antibiotics for ≥72 hours by 27% ( P = 0.002) with procalcitonin guidance. CONCLUSION: Procalcitonin guidance can safely reduce antibiotic usage when used to discontinue antibiotic therapy in adult ICU patients and when used to initiate or discontinue antibiotics in adult patients with respiratory tract infections. Journal of Hospital Medicine 2013;8:530–540. © 2013 Society of Hospital Medicine